2005
DOI: 10.1097/01.ta.0000159242.93309.f6
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Scanning and Selective Laparoscopy in the Diagnosis of Blunt Bowel Injury: A Prospective Study

Abstract: CT scanning and selective LP can prevent nontherapeutic laparotomy and delayed diagnosis in patients with suspected BBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
1
34
0
6
Order By: Relevance
“…The role of the CT scan in detecting BBMI remains controversial despite the improvements that have been made in terms of speed and image resolution with the advent of 32-and 64-detector helical scanners for the evaluation of intra-peritoneal and retro-peritoneal injuries [4,[11][12][13][14][15]. Our results indicate a high level of accuracy for detection of BBMI by CT scan, with a positive rate of 86%.…”
Section: Discussionsupporting
confidence: 51%
“…The role of the CT scan in detecting BBMI remains controversial despite the improvements that have been made in terms of speed and image resolution with the advent of 32-and 64-detector helical scanners for the evaluation of intra-peritoneal and retro-peritoneal injuries [4,[11][12][13][14][15]. Our results indicate a high level of accuracy for detection of BBMI by CT scan, with a positive rate of 86%.…”
Section: Discussionsupporting
confidence: 51%
“…Saku et al 19 analyzed the CT findings of 12 patients with SBI perforation due to blunt trauma, 5 of whom were given a pre-surgical follow-up CT. All 9 patients that were examined > 8 h post-injury, but none of the 4 examined within 4 h, presented with extraluminal air, suggesting that the incidence of extraluminal air increases as time elapses, prompting the authors to recommend a repeat CT, particularly after 8 h, in suspect cases to increase sensibility 19 . Mitsuhide et al 20 suggested the use of a repeat CT scan or laparoscopy to prevent nontherapeutic laparotomy and delayed diagnosis in patients with suspected blunt SBI. In our series, the falsenegative CT scan rate was 13%, consistent with previously published rates 1,14,17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…[15] In patients with a suspicion of hollow viscus injury, CT and diagnostic laparoscopy can be used for diagnosis. [19,20] In our study, we operated on five of eight patients with intestinal injury due to peritonitis-related signs, as revealed by repeated physical examination sessions. Diagnostic laparoscopy was performed to one of these patients.…”
Section: Discussionmentioning
confidence: 99%